Influence of preoperative skin sealing with cyanoacrylate on microbial contamination of surgical wounds following trauma surgery: a prospective, blinded, controlled observational study - Georg Daeschlein; Matthias Napp; Ojan Assadian; Jessica Bluhm; Colin Krueger; Sebastian von Podewils; Denis Gümbel; Peter Hinz; Hermann Haase; Pascal M. Dohmen; Torsten Koburger; Axel Ekkernkamp; et al. (International Journal of Infectious Diseases, 2014)
Objective: Intraoperative bacterial contamination is a risk factor for surgical site infections (SSIs). This prospective, randomized, blinded, controlled trial (Reg. No. BB08/12) investigated the effect of a cyanoacrylate-based skin sealant (InteguSeal) on intraoperative wound contamination during trauma surgery. Methods: A total of 128 patients undergoing trauma surgery were assigned randomly to an intervention (n = 62) or a control group (n = 66). Surgical sites were investigated at three locations: maximum incision depth (base), wound margin prior to wound closure (margin), and the surgical sutures (suture). Colony-forming units (CFU) were counted after 48 h of incubation. Results: Overall, significantly lower CFU counts were obtained for samples from the intervention group at all three sample sites compared to the control group. The difference, however, was only significant for the suture site (p = 0.040). Conclusions: Preoperative sealing reduced microbial contamination on sutures during surgery, while the overall wound contamination remained unchanged. Hence, prevention of the clinically more relevant deep SSIs may not be expected. However, this study was not designed to detect differences in the rate of SSI. The role of the reduction in suture contamination with regard to the prevention of SSI remains to be evaluated.